2007
DOI: 10.1371/journal.pone.0000846
|View full text |Cite
|
Sign up to set email alerts
|

Host-Plant Selectivity of Rhizobacteria in a Crop/Weed Model System

Abstract: Belowground microorganisms are known to influence plants' performance by altering the soil environment. Plant pathogens such as cyanide-producing strains of the rhizobacterium Pseudomonas may show strong host-plant selectivity. We analyzed interactions between different host plants and Pseudomonas strains and tested if these can be linked to the cyanide sensitivity of host plants, the cyanide production of bacterial strains or the plant identity from which strains had been isolated. Eight strains (four cyanide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…1 and 3): 2 mol of chemically supplied HCN resulted in 6% of growth compared to the control, but when plants were grown in the presence of strains producing a similar quantity of HCN (PUPa3 and CV0), plant biomass was five times higher (30% of the control biomass). Similar observations were made in the field, where external application of HCN proved much more plant growth inhibitory than cyanogenesis by inoculated rhizosphere pseudomonad populations (53). In addition to the putative production of growth promoting volatiles by the bacterial strains, which could counteract the negative effect of HCN, the different timing dynamics of application is likely to account in great part for the differences observed in plant responses.…”
Section: Vol 77 2011 Hcn and Phytotoxicity Of Bacterial Volatiles 1005supporting
confidence: 70%
“…1 and 3): 2 mol of chemically supplied HCN resulted in 6% of growth compared to the control, but when plants were grown in the presence of strains producing a similar quantity of HCN (PUPa3 and CV0), plant biomass was five times higher (30% of the control biomass). Similar observations were made in the field, where external application of HCN proved much more plant growth inhibitory than cyanogenesis by inoculated rhizosphere pseudomonad populations (53). In addition to the putative production of growth promoting volatiles by the bacterial strains, which could counteract the negative effect of HCN, the different timing dynamics of application is likely to account in great part for the differences observed in plant responses.…”
Section: Vol 77 2011 Hcn and Phytotoxicity Of Bacterial Volatiles 1005supporting
confidence: 70%
“…Pathogenic fungi are most often specifically examined in feedback studies and in some cases their effect has been directly demonstrated (Mills and Bever 1998, Packer and Clay 2000, Klironomos 2002. In a separate experiment, Zeller et al (2007) showed that the biomass of the species with the greatest negative soil feedback, Echinochloa crus-galli, is reduced by 90% when infected with a cyanide-producing Pseudomonas bacterial strain. In our study, we were unable to attribute the effect to soil fungi.…”
Section: Discussionmentioning
confidence: 99%
“…However, several attempts to utilize only chitinolytic bacteria as biological control agents have failed (35,40). One reason for these failures is that both colonization and chitinase production by the bacteria in rhizospheres are affected by various factors including plant species, cultivars, the physiological condition of plants, soil type and indigenous microorganisms (16,19,33,45).…”
Section: Discussionmentioning
confidence: 99%